Implementation Status of Tobacco-free Education Institutional Guidelines at Schools in Rural Areas of District Saharanpur, Uttar Pradesh - Sanjeev K Singh; Mohit Wadhawan; Amit M Varshney; Amit Kumar (Journal of South Asian Association of Pediatric Dentistry)
Background: The tobacco-free educational institution (ToFEI) guidelines by the Government of India (GOI) can be used by schools as a self-evaluation scorecard to assess the implementation status of these guidelines. Aim: This observational study assessed the school's adherence to the ToEFI guidelines in the district of Saharanpur, Uttar Pradesh, India. Materials and methods: Around 102 schools (62 government and 40 private) were conveniently selected in a block. None of the schools fulfilled the criteria of mandatory scores. The government schools (32.87 ± 20.97) scored significantly more than private schools (20.45 ± 13.31) for overall ToFEI scores (p = 0.001). The mean mandatory ToFEI scores observed in the government and private schools were 18.71 ± 14.87 and 9.0 ± 7.08, respectively (p = 0.001). None of the schools have marked a 100-yard area from the outer limit of the boundary wall/fence of the educational institute. Conclusion: The mean ToFEI scores were very low among the schools included (28.0 ± 19.27). The alarming situation calls for integrating the ToFEI agenda into regular school-based programs and assisting schools in attaining a tobacco-free status.